Socio-economic evaluation of furniture re-use - Granström, Fanny (2007)
The author adopted a case study approach to explore the complex phenomena of reuse. The author found that policies have significant impact on the scope for furniture re-use if driven by LCA. LCA could be considered to evaluate the offset utility of reuse. The author found that for example consumer behaviour is affected by socio economic factors such as income that in turn affect the product offset by re-using furniture and the outcome of an LCA. Re-use tends to arise from lower income groups, but this should not be exclusive. Re-use does not necessarily reduce demand for new furniture or reduce waste going to landfill in the long run but is a waste treatment method that can be justified from a socio economic perspective. Donators and recipients have further more different motives for using NOAH in terms of re-use of furniture. It is recommended for future research to understand policy development options for re-use of furniture and also how Local Authority options influences the role of the intermediary such as community waste schemes.